EVALUASI TOTAL BAKTERI DAN BAKTERI PELARUT FOSFAT PADA RHIZOSFIR TANAMAN Stylosanthes guianensis, Gliricidia sepium, Bracharia decumbens, dan Pennisetum purpureum DI LAHAN KERING PADA MUSIM HUJAN - Diningtyas A.S.; I W. Suarna; S.A. Lindawati (Udayana University, 2018)
Phosphate solubilized bacteria is bacteria that useful to solve P bound to be P elements which could be absorped by plant. So, this research is needed to know total population of bacteria and phosphate solubilized bacteria in plants rhizosfer at dry land in rainy season. The research followed aditive linier model with assumption phosphate solubilized bacteria population caused by different of plant species only. Samples taken were consisted of 5 treatments in plants rhizosfer i.e. non rhizosfer (NR), Stylosanthes guianensis (Sg), Gliricidia sepium (Gs), Brachiaria decumbens (Bd), and Pennisetum purpureum (Pp) with 4 replications. Variable observed were Total Plate Count (TPC), total of Phosphate Solublilized Bacteria (PSB), P element (phosphore) ail water content. The research results showed that the TPC of land about 1.06 - 7.12 × 107 cfu/g, PSB about 4.78 - 7.60 × 106 cfu/g. P element at treatment NR was the highest 12,16 ppm. The highest soil water content on the treatment Bd was 4.86%. It can be concluded that TPC and BPF in non rhizosphere and rhizosphere of plants Sg, Gs, Bd and Pp on dry land in the rainy season are different. The content of P elements ranged from 6.14 to 23.07 ppm and the moisture content ranged from 1.68 to 4.86%. Key words: phosphate soluble bacteria, non rhizosfer, rhizosfer